MEKANISME KEBIJAKAN DEVIDEN DAN PENGARUHNYA TERHADAP NILAI PERUSAHAAN - Desmiza Desmiza (Universitas Islam Bandung, 2014)
Dividend policy concerns to the company's act to share profits or to hold it as retained earnings. Dividend distribution to the shareholders depends on the policy of each company, so it requires serious concideration by the management. The greater the dividend distributed to shareholders, the less retained earnings. Furthermore, it will reduce the total internal funding sources which aim to reduce the ability of the company to invest and it will lower the growth rate of the company. And all of things above will lead to decreasing of company 's shares’ value. Therefore, management is required to be able to determine the optimal dividend policy which create a balance between current dividends and the growth expectations in the future. The company needs to concider various influential factors in order to maximize the value of the company